Cost-effectiveness of Pancreatic Cancer Surveillance in High-Risk Individuals: An Economic Analysis. Issue 4 (April 2019) - Corral, Juan E.; Das, Ananya; Bruno, Marco J.; Wallace, Michael B.
Abstract : Objective: The aim of the study was to perform an economic analysis to identify the clinical and cost determinants of pancreatic cancer (PC) surveillance in high-risk individuals (HRIs). Methods: A Markov model was created to compare the following 3 strategies: no screening, endoscopic ultrasound (EUS), and magnetic resonance imaging (MRI) screening. Patients were considered HRIs according to the Cancer of the Pancreas Screening consortium recommendations. Risk for developing PC, survival, and costs data were obtained from the Surveillance, Epidemiology, and End Results and Medicare databases. Surveillance effectiveness was obtained from a recent meta-analysis. Results: Analysis of a cohort with fivefold relative risk of PC higher than the US population showed that MRI is the most cost-effective strategy. For those with the highest risk (>×20 relative risk), EUS became the dominant strategy. Our model was impacted by cost and imaging performance, but still cost-effective within the range reported in literature. Threshold analysis showed that if MRI increases greater than US 1600, EUS becomes more cost-effective. Once patients reached the age of 76 years, "no screening" was favored. Both surveillance strategies were cost-effective over a wide range of willingness to pay. Conclusions: Abdominal imaging followed by pancreatectomy is cost-effective to prevent PC in HRIs, favoring MRI in moderate risk cases but EUS in those with highest risk. Abstract : Supplemental digital content is available in the text.